European Regional Differences in All‐Cause Mortality and Length of Stay for Patients with Hip Fracture. (December 2015) - Medin, Emma; Goude, Fanny; Melberg, Hans Olav; Tediosi, Fabrizio; Belicza, Eva; Peltola, Mikko; ,
Summary: The objective of this study was to compare healthcare performance for the surgical treatment of hip fractures across and within Finland, Hungary, Italy, the Netherlands, Norway, Scotland, and Sweden. Differences in age‐adjusted and sex‐adjusted 30‐day and one‐year all‐cause mortality rates following hip fracture, as well as the length of stay of the first hospital episode in acute care and during a follow up of 365 days, were investigated, and associations between selected country‐level and regional‐level factors with mortality and length of stay were assessed. Hungary showed the highest one‐year mortality rate (mean 39.7%) and the lowest length of stay in one year (12.7 days), whereas Italy had the lowest one‐year mortality rate (mean 19.1 %) and the highest length of stay (23.3 days). The observed variations were largely explained by country‐specific effects rather than by regional‐level factors. The results show that there should still be room for efficiency gains in the acute treatment of hip fracture, and clinicians, healthcare managers, and politicians should learn from best practices. This study demonstrates that an international comparison of acute hospital care is possible using pooled individual‐level administrative data. Copyright © 2015 John Wiley & Sons, Ltd.